2016
DOI: 10.24264/icams-2016.vi.2
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Consumption and Ethical Behavior of Consumers in the Footwear Industry

Abstract: Traditionally shoes are made from leather and most of the worldwide population wear it, but there is a particular group of consumers, with an ethical behavior, who prefer shoes made from alternative materials. In our days, the main objective of the fashion industry (T&C, footwear) is to reduce the intensive use of fossil energy, non-renewable raw material and decreasing of landfill waste. In past years, sustainable and ethical consumption has become a popular topic in industries, has gained increasing importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
2
2
0
2
Order By: Relevance
“…The respondents suggested that all the proposed alternative consumption scenarios are comparatively more sustainable compared to the traditional ways of selling footwear for various reasons such as extending the useful life (scenarios: maintenance and repair, takeback), recycling (scenarios: takeback, personalization), belongingness (scenarios: assembled, customized, and personalized), informed utilization (scenario: advice and consultancy), and enhanced utilization (scenarios: renting, sequential sharing, swapping, and functionality). Furthermore, we identified that sustainability within the footwear ecosystem must also consider factors such as price, style, fashion, and personal comfort and confirmed the findings by a previous study (Luca & Loghin, 2016). The proposed alternative footwear consumption scenarios effectively address these factors alongside sustainability, providing a promising way forward.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The respondents suggested that all the proposed alternative consumption scenarios are comparatively more sustainable compared to the traditional ways of selling footwear for various reasons such as extending the useful life (scenarios: maintenance and repair, takeback), recycling (scenarios: takeback, personalization), belongingness (scenarios: assembled, customized, and personalized), informed utilization (scenario: advice and consultancy), and enhanced utilization (scenarios: renting, sequential sharing, swapping, and functionality). Furthermore, we identified that sustainability within the footwear ecosystem must also consider factors such as price, style, fashion, and personal comfort and confirmed the findings by a previous study (Luca & Loghin, 2016). The proposed alternative footwear consumption scenarios effectively address these factors alongside sustainability, providing a promising way forward.…”
Section: Discussionsupporting
confidence: 89%
“…Such a huge demand for footwear products is attributed to several reasons, such as an increase in the per capita income in both developed and developing economies (Felton, 2018), rapid changes in footwear fashion (Luca & Loghin, 2016; Majima, 2008), demand for designer shoes (Felton, 2018), and reduced lifecycle of the footwear due to the high responsiveness to consumer demands (Staikos & Rahimifard, 2007b). Another reason for such an increased demand is that consumers, especially in developing countries, often do not consider the environmental perspective when purchasing fashion goods such as footwear (Baier et al, 2020; Bernardes et al, 2018), and the footwear preference is primarily based on price, style, and personal comfort (Luca & Loghin, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Consumers of high-end, sustainable footwear are becoming increasingly interested in customisation choices . This interest is driven by a desire for unique, personalised products that align with their ethical and sustainable values (Luca & Loghin, 2016). This feature gives customers the ability to influence the style and customisation of their shoes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Si bien algunos consumidores pueden interpretar la RSE de las empresas de lujo como una práctica opcional y por lo tanto inútil, los consumidores en su conjunto están cada vez más interesados en las políticas sociales y ambientales (Luca y Loghin, 2016;Wagner et al, 2017) , por lo que esperan que las empresas no solo se adhieran a las regulaciones, sino que también apoyen programas filantrópicos, preserven el medioambiente y cooperen con las instituciones locales (Blaauwbroek, 2003). En respuesta, muchas empresas de lujo ahora posicionan la ética y la responsabilidad como valores corporativos primarios.…”
Section: Análisis De Los Clústeres (T2)unclassified
“…El tercer clúster (azul) consiste de 18 ítems, en los cuales se destacan elementos enlazados hacia los aspectos económicos de la producción, básicamente hacia todos los ejercicios de gestión de la sostenibilidad, los cuales podemos ver como los esfuerzos económicos y sociales de la industria hacía los elementos environmental, social and governance (ESG), así como enlaces hacia las formas de planeación estratégica de la producción explicadas por (Berger-Douce y Deschamps, 2012; Figura 6. Mapa bibliográfico de co-ocurrencia por temas Santos, 2011) que desembocan en discursos como el consumo sostenible y la producción sostenible (Grazzini et al, 2021;Luca y Loghin, 2016) y una industria encaminada hacia elementos ecoamigables dentro de un mercado verde.…”
Section: Análisis De Los Clústeres (T2)unclassified